The impact of collaboration strategy in the field of innovation on the effectiveness of organizational structure of healthcare institutions - Grynko, Tetiana; Shevchenko, Tetiana; Pavlov, Roman; Shevchenko, Vladyslav; Pawliszczy, Dariusz (Knowledge & performance management (Online), 2020)
The need for innovative development of healthcare institutions is determined by the necessity to increase the efficiency of organizational processes based on the formation of new models of cooperation, which will make it possible to get access to new technologies and knowledge. The goal of the study is to determine the parameters of the impact of innovative open cooperation strategy and the strategy of innovative closed cooperation of healthcare institutions on the effectiveness of their organizational structure in the context of dissemination and the use of knowledge. Simulation modeling was applied to generate the most effective organizational management structure in the context of innovative cooperation and knowledge exchange within the organizational processes “Inside-out” and “Inside-in”. It is substantiated that the strategies of innovative cooperation “Open Innovation/Closed Innovation” have a significant impact on the organizational structure of management of healthcare institutions in terms of the “degree of centralization” (Dci), “degree of mediation” (Dii), and “degree of centralization of powers” (Dpi). The values of the selected criteria range from 25,52% to 61,50% in the case of Dii, and from 34,53% to 52,63% in the case of Dci, which indicates a higher efficiency of organizational knowledge exchange processes in healthcare institutions, which adhere to the Open Innovation strategy of innovative cooperation. Therefore, there are significant differences in the effectiveness of the management’s organizational structure depending on the degree of openness of innovative cooperation of healthcare institutions. The strategy of innovative openness allows increasing the number and quality of connections in the context of knowledge exchange between the subjects (actors, agents) of the organizational structure (in a broad sense, considering internal and external levels of externality) of healthcare institutions, regardless of the distance between them and the level of similarity.